2003
DOI: 10.1016/s0210-4806(03)72906-4
|View full text |Cite
|
Sign up to set email alerts
|

Finasterida: Diez Años De Uso Clínico. Revisión Sistemática De La Literatura

Abstract: Finasteride, through prostate volume reduction, modify natural evolution of BPH, decreasing the risk of acute urine retention and surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Fifteen systematic reviews or meta-analyses of 5α-RI clinical trial reports each concluded that 5α-RI-associated sexual adverse events are infrequent, mild, and reversible. None of these prior meta-analyses assessed the adequacy of evaluation of adverse events in primary clinical trial reports (Boyle, Gould & Roehrborn, 1996; Chin, 2013; Edwards & Moore, 2002; Gacci et al, 2014; Gupta & Charrette, 2014; Jimenez Cruz, Quecedo Gutierrez & Del Llano Senaris, 2003; Mella et al, 2010; Oelke et al, 2015; Park & Choi, 2014; Tacklind et al, 2010; Trost, 2013; Varothai & Bergfeld, 2014; Wu et al, 2014; Yin et al, 2015; Yuan et al, 2015). A meta-analysis of clinical trials in men with prostatic hyperplasia found that the risk of ED was significantly increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Favilla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen systematic reviews or meta-analyses of 5α-RI clinical trial reports each concluded that 5α-RI-associated sexual adverse events are infrequent, mild, and reversible. None of these prior meta-analyses assessed the adequacy of evaluation of adverse events in primary clinical trial reports (Boyle, Gould & Roehrborn, 1996; Chin, 2013; Edwards & Moore, 2002; Gacci et al, 2014; Gupta & Charrette, 2014; Jimenez Cruz, Quecedo Gutierrez & Del Llano Senaris, 2003; Mella et al, 2010; Oelke et al, 2015; Park & Choi, 2014; Tacklind et al, 2010; Trost, 2013; Varothai & Bergfeld, 2014; Wu et al, 2014; Yin et al, 2015; Yuan et al, 2015). A meta-analysis of clinical trials in men with prostatic hyperplasia found that the risk of ED was significantly increased with combined 5α-RI plus α 2 adrenergic receptor blocker compared to α 2 adrenergic receptor blocker alone (Favilla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%